The Role of 18-Fluoro-2-Deoxy-Glucose Positron Emission Tomography/Computed Tomography as Response and Prognosis Predictive Factor of Concurrent Chemoradiotherapy after Induction Chemotherapy in Head and Neck Squamous Cell Carcinoma: A Prospective Study - Šedienė, Severina (Medicina (Kaunas), 2018)
Background and objectives: The importance of induction chemotherapy (ICT) followed by concurrent chemoradiotherapy (CCRT) has been re-established in recent years aiming at fewer metastatic sites and better control of the disease. We prospectively studied the possibility of early prediction of overall survival (OS) and progression-free survival (PFS) after 3 cycles of chemotherapy with doxetacel, cisplatin and 5-fluorouracil using 18-fluoro-2-deoxy-glucose positron emission tomography computed tomography ((18)F-FDG PET/CT) in patients with head and neck squamous cell cancer. To our knowledge, this is the first such study. Materials and Methods: Thirty-five patients were studied. They underwent an (18)F-FDG PET/CT examination twice: a day before ICT and 10–14 days after the last cycle of ICT. Tumor-standardized uptake value (SUVmax) and hypermetabolic tumor volume were measured on both scans. The mean age of patients was 56.5 years. Complete responses to CCRT PFS and OS were calculated. Results: Our results showed that a decrease of ≥30% in the SUVmax value after ICT was a prognostic factor of tumor response to PFS and OS (p = 0.026 and p = 0.021). The groups of patients with a SUVmax between 10 and 14.5 in the primary tumor on a pre-ICT (18)F-FDG PET/CT scan had statistically shorter PFS and OS (p = 0.001, p = 0.006) when compared with other groups of patients with SUVmax less than 10 or SUVmax more than 14.5. A decrease of less than 55% of hypermetabolic tumor volume of the primary tumor was significantly related to poor prognosis in PFS and OS (p = 0.033, p = 0.017). Conclusions: SUVmax and hypermetabolic tumor volume measured on (18)F-FDG PET/CT after ICT might be valuable prognostic tools for predicting OS and PFS and, thus, for the selection of patients with head and neck cancer who will benefit from CCRT.